Vocational Middle-school Internship with Industry During the Covid-19 Pandemic - Purwanto, Dedi; Lubis, Muhammad Ripqi; Sultono, Sultono (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
The Covid -19 pandemic has influenced all levels of education, even at the vocational level, especially in the industrial world internship program. Industry parties still need to be ready to accept participant apprenticeships with base guard happening the spread of the covid virus. This paper aims to give solutions in the implementation apprenticeship industry at vocational schools during the Covid-19 pandemic. Apprenticeships aim to fulfill demands of competence in the curriculum implementation in the world of work and experience work. The research adopted a qualitative approach with literature study and descriptive analysis method. The study results revealed that internship-based Project Based Learning is one of the solutions for implementing internships during the Covid-19 pandemic. The internship-based also optimizes the concept of a teaching factory at the vocational school level that leverages the participatory education practices involving vocational schools with the industries.